PERSEPSI GURU DAN SISWA TERHADAP MEDIA INTERAKTIF DALAM PROSES PEMBELAJARAN - Asha Sasmita; Saugadi; Arham Rahim (Program Studi Teknologi Pendidikan Universitas Madako Tolitoli, 2025)
This study aims to describe teachers' and students' perceptions of the use of interactive learning mediain the learning process at SDN Salugan. This study uses a qualitative approach. Data collectiontechniques were carried out through observation, interviews, and documentation, which were thenanalyzed using qualitative descriptive analysis. The results of the study show three main findings. First,teachers and students have positive views of interactive learning media. Media such as animated videos,interactive PowerPoint presentations, and digital quizzes are considered capable of increasing studentmotivation and understanding and creating a more enjoyable learning atmosphere. Second, teachersalready have experience using interactive media and are able to adjust its use to the needs of thematerial and characteristics of the students, although this has not been done routinely. Third, thechallenges faced include infrastructure limitations (projectors and internet connections), lack oftechnology training for teachers, and adjustments made by students to media-based learning processes.